2020
DOI: 10.7717/peerj.8557
|View full text |Cite
|
Sign up to set email alerts
|

LINC00958 and HOXC13-AS as key candidate biomarkers in head and neck squamous cell carcinoma by integrated bioinformatics analysis

Abstract: Background Head and neck squamous cell carcinoma (HNSCC) is a malignant tumor with a strong tendency for metastasis and recurrence. Finding effective biomarkers for the early diagnosis of HNSCC is critical for the early treatment and prognosis of patients. Methods RNA sequencing data including long non-coding RNAs (lncRNAs), messenger RNA (mRNAs) and microRNAs (miRNAs) of 141 HNSCC and 44 adjacent normal tissues were obtained from the TCGA.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…This study reported the clinical significance, in vivo and in vitro functions, and mechanisms of LINC00958 in LUAD. Consistent with the previously reported function of LINC00958 as an oncogene in other cancer types (18,19,(33)(34)(35)(36)(37)(38)(39)(40), this study demonstrated that LINC00958 promotes lung cancer growth and metastasis and inhibits cancer cell apoptosis. This suggested that LINC00958 has a potent tumorigenesis role in cancer.…”
Section: Discussionsupporting
confidence: 92%
“…This study reported the clinical significance, in vivo and in vitro functions, and mechanisms of LINC00958 in LUAD. Consistent with the previously reported function of LINC00958 as an oncogene in other cancer types (18,19,(33)(34)(35)(36)(37)(38)(39)(40), this study demonstrated that LINC00958 promotes lung cancer growth and metastasis and inhibits cancer cell apoptosis. This suggested that LINC00958 has a potent tumorigenesis role in cancer.…”
Section: Discussionsupporting
confidence: 92%
“…To the best of our knowledge, this is the first report showing the physiological role played by HOXC13-AS. This lncRNA has been previously identified as a cancer biomarker in cervical cancer 52 , breast cancer 53 , glioma 54 , hepatocellular carcinoma 55 , cholangiocarcinoma 56 , and head and neck squamous cell carcinoma [57][58][59] , which emphasizes the absence of HOXC13-AS expression in most normal tissues except the skin. Additionally, HOXC13-AS reportedly functions as an oncogene promoting proliferation and the epithelial-mesenchymal transition of cancer cells 57 .…”
Section: Discussionmentioning
confidence: 96%
“…Long noncoding RNAs (LncRNAs) were considered as vital regulators in the tumorigenesis and progression of a variety of malignancies, including NPC ( 6 8 ). Previous studies have discovered that a few dysregulated lncRNAs are related to NPC progression via regulating cell proliferation, apoptosis, migration, invasion and drug resistance, such as AFAP1-AS, LET, LINC00958 and HOXC13-AS ( 9 11 ). LncRNA CASC9 was firstly reported in esophageal squamous cell carcinoma as an oncogene in 2015, and was subsequently confirmed to be associated with tumorigenesis and progression of malignant tumors including gastric cancer, hepatocellular carcinoma and breast cancer ( 12 14 ).…”
Section: Introductionmentioning
confidence: 99%